PENGARUH SUHU DAN LAMA PEMANASAN EKSTRAKSI TERHADAP RENDEMEN DAN MUTU ALGINAT DARI RUMPUT LAUT HIJAU Sargassum sp - Angga Sukma, I Wayan; Admadi Harsojuwono, Bambang; Arnata., I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 1 (2017): Maret, 2017)
The purpose  of this study was to determine the effect of temperature and heating times of extraction and their interactions to the yield and quality of alginate from seaweed green Sargassum  sp, determine the temperature and duration of heating extraction of the right to produce a high yield and the best quality alginate from seaweed green Sargassum  sp. This study uses a Randomized Block Design (RBD) factorial treatment comparison of temperature and heating times extraction (60;5, 60;10, 60;15, 70;5, 70;10, 70;15, 80;5, 80;10, 80;15, 90;5, 90;10, 90;15) are grouped into 2 treatment so obtained 24 experimental units. The variables measured in this study is the yield, moisture content, ash content, viscosity, pH, and the functional group (FTIR). The results showed that the  extraction temperature alginate significant effect on yield and moisture content, duration of heating extraction very significant effect on ash content, temperature and duration of heating extraction and its interactions very significant effect on the viscosity, the functional groups, except for pH. Temperature 80°C and heating times extraction of 15 minutes  to produce alginate best with 1,95% yield characteristics, 8,51% moisture content, ash content of 8,92%, viscosity  16 cp, pH 5,50. Alginate extraction  results obtained interpretations are hidroxyl functional groups (O-H), group alkanes (C-H), a triple  bond (C?N), carboxyl group (-COOH), and a fingerprint region mannuronic. Keywords: Green Seaweed Sargassum sp, Extraction alginate
Keywords: 131